Dental tray adhesives and their role as potential transmission medium for microorganisms - Schierz, Oliver; Müller, Henrik; Stingu, Catalina Suzana; Hahnel, Sebastian; Rauch, Angelika (Clinical and experimental dental research, 2021)
Objectives This study aimed to evaluate the possible ability of dental impression tray adhesives to serve as a transmission medium for bacteria and fungi when reusable adhesive applicators are utilized. Materials and methods Ten flasks with tray adhesive were monitored over a period of 12 weeks during clinical use for contamination with bacteria or fungi. Adhesive fluid samples were cultivated on eight different culture media. All grown colonies were identified by using mass spectrometry (MALDI‐TOF). Isolates without reliable identification were either identified by Rapid ID 32 API‐STREP V3.0 or by sequencing the 16S rRNA genes. Results After 4 weeks, bacterial growth was detected on chocolate blood agar plates in five different samples. The bacterial species were identified as Staphylococcus warnerii, Staphylococcus epidermidis, Staphylococcus pasteuri, Ralstonia insidiosa, and Alloiococcus otitidis. After 8 weeks Streptococcus oralis grew on a blood agar plate. In all samples, no fungi were identified. Conclusions The disinfectant component of the tested tray adhesive seems to be effective. However, some bacteria survived in the flask for a clinically relevant time, which might result in a potential transmission to a new host.